Implementasi Metode Sugestopedia dalam Pembelajaran Apresiasi Puisi pada Mahasiswa Program Studi Pendidikan Bahasa Indonesia - Prawoto, Eko Cahyo; Pramulia, Pana; Rohmah, Nur; Indayani; Ardhianti, Mimas (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
Literary appreciation learning is an effort to increase competence in the field of literature so that Indonesian Language Education Study Program students have complete provisions as prospective educators to be implemented in school. However, in the process there are learning problems that arise, including low motivation of students in getting to know literary works of poetry and lack of knowledge when students appreciate poetry. For this reason, further research is needed to overcome this problem by learning through the application of the suggestopedia method. The research method used is a qualitative descriptive method, with research subjects being students of the Indonesian Language Education Study Program. Data collection techniques were carried out using documentation techniques for analyzing poetry tasks, while data analysis techniques were carried out using quantitative descriptive techniques. Based on the research, it is known that the application of the suggestopedia method can increase students' competence in appreciating poetry. This can be proven by the average score obtained during the pre-test which the average is 2.5 (the scoring guideline 1-5), while the results during the post-test or after applying the suggestopedia method in student learning obtained an average score 4.